(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Unfortunately, the most commonly used today is the concept of postmodernism. Postmodernism of the 20th century in the spheres of culture at the end of the century, art, philosophy, science and politics a wide range of phenomena occurring in society. The main problem of postmodernism is the lack of a clear understanding of the meaning, clear and fascinating, TV is often heard in movies, in magazines, in art, in literature.